Implementasi Maqâs?id al-Ah?kâm Terkait Rekontruksi Hukum Islam Indonesia - Khoirul Amin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2014)
Maqâs?id sharî’ah is the result of ijtihâd priest Shâtibî in formulating the standard value intended by sharî’. Maqâs?id Sharî’ah is a philosophical review that gives a charge to the essential substance of the law, through an approach legal review itself. Maqâs?id al-ah?kâm considered as a basis for the establishment of a law, and can be categorized as the primary basis in law. By considering several postulations texts and findings of thought in both the conservative position, modern or liberal, can find common ground that can be justified academically in relation to maqâs?id sharî’ah. This study resulted in the finding that the application relates to the community because there are reasons want it fixed by the general mas?lah?ah. In practice, most of the laws of the sharî’ah is devoted to the Prophet Muhammad; and the other half is devoted to an event. Sharî’ah is a tangle of ropes across place and time keeping in mind the past, for the sake of its application in the present and that will come. The basic principles of sharî’ah, can be found the conclusion that al-kulliyyât al-khams that in its application, must consider the aspect al-d?arûriyyat, al-h?âjiyyat and at-tah?siniyyat.